Development of High-Entropy Alloy Coating by Additive Technology - Kocsis, Bence; Gulyás, Gábor; Varga, Lajos Károly (Frontiers in Materials, 2022)
In this research study, various additively fabricated coatings and bulk 3D printed parts were prepared, using the mechanical and corrosion resistant properties of CrMnFeCoNi (Cantor-alloy) and AlCrMnFeNi high-entropy alloys. The coatings were applied to an EN 1.0038 carbon steel substrate using direct metal laser sintering (DMLS). We attempted to optimize the 3D printing parameters of HEA alloys. The effect of volumetric energy density (VED) on the microstructure was investigated by scanning electron microscopy. We also examined the change of relative concentration of alloys in direction of 3D printing (z–axis) as well as the volumetric failures (cracks and gaps). Standard salt spray tests were performed to test the corrosion resistance of various coatings after 3D printing. The use of both raw materials applied as thick films was successful; they retained their corrosion-resistant properties even with a change in their composition. Regarding its crystal structure, no difference was found between the base material and the material applied as a coating on the basis of X-ray diffraction investigations. Bulk HEA printing experiments need further optimization concerning their structural integrity and density in the case of Cantor-alloy. Bulk 3D printing experiments of AlCrMnFeNi alloy did not yield satisfactory results because of the formation of dendritic microstructure, brittle BCC phase and the residual internal stresses resulted in part distortion and improper printing.